The Production of Homo Sacer in the Dutch East Indies Government: An Examination of "Cerita dari Digul" edited by Pramoedya Ananta Toer - Anggit Febrianto (Journal of Translation, Linguistics and Literature, 2024)
Digul was an internment camp built to exile those who were considered involved or sympathetic to the 1926-1927 rebellion. Those who became victims can be called homo sacer because they were arrested and exiled without going through a court process. The events in the exile to Digul were later immortalized into literary works in the form of prose, and in 2001, collected and edited by Pramoedya Ananta Toer into a book entitled Cerita dari Digul. This research aims to analyze how the Dutch East Indies government produced homo sacer in the book Cerita dari Digul. This research uses a qualitative method. The data collection technique is carried out using the literature study method, namely by careful and thorough reading of the material object. The data that has been collected will then be analyzed using Giorgio Agamben's Homo Sacer Theory. The conclusion of the research is: in Cerita from Digul, the Dutch East Indies Government produced homo sacer using a condition commonly referred to as state-of-exception. That is, a kind of state of emergency or critical situation, which in the name of this critical situation, the state in the name of safeguarding rights, then deprives rights. Those who were arrested, transported and exiled to Digul were not people who were considered dangerous, let alone had committed dangerous acts. They were arrested and exiled only because they had entered associations that were deemed dangerous to the public peace.